Native Presence and Sovereignty in College: Sustaining Indigenous Weapons to Defeat Systemic Monsters - Sicka, Bhavika (Journal of International Students, 2022)
In Native Presence and Sovereignty in College: Sustaining Indigenous Weapons to Defeat Systemic Monsters, Amanda Tachine delineates the barriers that hinder the personal and academic goals of Navajo students, and what sources of strength and comfort these students channel to guide them toward college. Tachine stresses the importance of story-sharing and world-making, which she herself employs. She uses a story rug technique, weaving together the narratives of ten Navajo students as they journey to and through college, bringing together their experiences of belonging in educational settings and offering us lessons gleaned. The storylines serve as threads, which she connects to construct collective themes as part of a larger tapestry.